2002
DOI: 10.1038/sj.leu.2402697
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Ink4-locus (the p16ink4a, p14ARF and p15ink4b genes) predicts relapse in children with ALL treated according to the Nordic protocols NOPHO-86 and NOPHO-92

Abstract: Inactivation of the Ink4 gene locus locus on 9p comprising the tumour suppressor gene p16ink4a and its neighbours p14ARF and p15ink4b is common in childhood acute lymphoblastic leukaemia (ALL), but the prognostic significance is controversial. DNA from 230 patients was retrospectively analysed by Southern blotting, single strand conformation polymorphism (SSCP) and sequencing techniques. The results were correlated with clinical characteristics and outcome. One hundred and ninetyfour fully analysed patients, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 36 publications
1
8
2
Order By: Relevance
“…We did not find an association between clinical outcome and extensively studied loci such as CDKN2A/B 32,33 or PAX5 status, despite the finding that PAX5 alterations were the most common lesions in the B-cell–differentiation pathway in both cohorts. PAX5 alterations may be important in establishing the leukemic clone, whereas alterations of IKZF1 may also contribute to resistance to chemotherapy.…”
Section: Discussioncontrasting
confidence: 89%
“…We did not find an association between clinical outcome and extensively studied loci such as CDKN2A/B 32,33 or PAX5 status, despite the finding that PAX5 alterations were the most common lesions in the B-cell–differentiation pathway in both cohorts. PAX5 alterations may be important in establishing the leukemic clone, whereas alterations of IKZF1 may also contribute to resistance to chemotherapy.…”
Section: Discussioncontrasting
confidence: 89%
“…CDKN2A deletion was described to be associated with adverse clinical features, higher WBC counts, and leukemic cell burden in previous reports, but the prognostic impact of CDKN2A deletions as well as the status of homozygous deletion has been controversial . In the present study, we did not find an association between CDKN2A/2B deletion and the relapse or survival rate of our patients.…”
Section: Discussioncontrasting
confidence: 79%
“…In our BCP‐ALL patients, the 9p21 deletion was less frequent than previously reported (Mirebeau et al , 2006; Kuiper et al , 2007; Mullighan et al , 2007), being found in only two patients (patients 9 and 23). Although CDKN2A has been identified as a tumour suppressor gene, its role in leukaemia development and relapse still remains controversial (Calero Moreno et al , 2002; Mirebeau et al , 2006).…”
Section: Resultsmentioning
confidence: 99%